Long-term results of combined treatment of triple-negative breast cancer - Vinnyk, Yuriy; Vlasenko, Vadim; Baranova, Anna (ScienceRise: Medical Science, 2020)
The most dangerous immunohistochemical type of breast cancer is the triple-negative type. This subtype is detected in 10-20 % of breast cancer cases and is characterized by an aggressive clinical course with high proliferative activity and growth rate, which leads to more active surgical tactics and systemic treatment. The aim of the study was to study the long-term results of the combined treatment of triple-negative type of breast cancer in comparison with other immunohistochemical types. Materials and methods. The treatment results of 140 women with breast cancer who underwent radical surgery and were available for contact after 6 months and more after the operation were analyzed depending on the initial clinical and pathological parameters and treatment features using the methods of descriptive statistics, χ2 criterion and correlation analysis, survival tables and the Kaplan-Meier method. Results. During the analyzed period, distant metastases were detected in 5 (3.6 %), locoregional recurrence in 15 (10.7 %), 12 (8.6 %) patients died. Long-term results with triple-negative type of breast cancer are worse than with luminal forms. A significant dependence of survival on neoadjuvant chemotherapy was revealed. Radiation therapy, the volume of surgery (radical resection or radical mastectomy), breast reconstruction did not significantly affect the long-term result of treatment. Conclusion. Triple-negative type of breast cancer has the worst long-term results with an increase in the frequency of distant and locoregional metastases and a decrease in overall and relapse-free survival compared with luminal types. After neoadjuvant chemotherapy, the frequency of locoregional relapses decreases and the life expectancy of patients increases